Pengaruh Pemberian Dehydroepiandrosterone (DHEA) terhadap Aktivitas Peroksidasi Lipid dan Kadar Nitrit Oksida pada Aorta Tikus Wistar Jantan yang Terpapar Asap Rokok - Nila Ridhayani; Aryadi Arsyad; Yulia Yusrin Djabir (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2022)
The research aimed to investigate the effect of dehydroepiandrosterone (DHEA) on lipid peroxidation activity and nitric oxide concentration in the aorta of male Wistar rats due to exposure to cigarette smoke. This study was a laboratory experiment using 21 rats that were divided into 3 groups: KN-14 (negative control that is given smoke exposure within 14 days), DHEA-1 (15 mg/kgBW + smoke exposure for 14 days), and DHEA-2 (30 mg/kgBW + smoke exposure for 14 days). The exposure was carried out in 25-45 minutes with 4 cigarettes/day. Surgery was performed in the 15th days to remove the aorta to examine malondialdehyde (MDA) as a biomarker of lipid peroxidation and nitric oxide (NO) concentration using Enzyme-linked Immunosorbent Assay (ELISA). The results showed that a significant increase in MDA concentrations was found in the group administered with DHEA, particularly at a dose of 30 mg/kgBW (p<0.05). Meanwhile, the administration of DHEA at doses of 15 and 30 mg/kgBW did not have a significant effect (p>0,05) on aortic NO concentrations compared to the group KN-14. Therefore, it can be concluded that the administration of DHEA could increase lipid peroxidation activity, as indicated by a significant increase in aortic MDA concentrations, without affecting aortic NO concentrations in rats exposed to cigarette smoke for 14 days.Keyword: Dehydroepiandrosterone (DHEA), MDA, NO, lipid peroxidation, exposure of cigarettes smoke